Ethnobotanical study of medicinal plants used by the indigenous community of the western region of Mizoram, India - Laldinfeli Ralte; Hmingremhlua Sailo; Y. Tunginba Singh (BMC, 2024)
Abstract Background Plants have long been utilized as traditional medicines by the inhabitants. However, until recently, the traditional knowledge had not been extensively documented from the hilly state of Mizoram, India. The present study was designed to perform a quantitative analysis of ethnomedicinal plants used by Mizo tribes using quantitative ethnobotanical indices. The study attempts to find new ethnomedicinal plant species that could be a source for the discovery of new drug formulations. Methods The information was obtained through extensive and semi-structured interviews. Quantitative indices such as informant consensus factor (ICF), use value (UV), fidelity level (FL), relative frequency of citation (RFC), and relative importance index (RI) were used to quantify the advantages, significance, and coverage of ethnomedicine. All the collected data were analyzed using the ethnobotanyR package in R. Results A total of 124 ethnomedicinal plant species, distributed in 112 genera under 60 families, were documented from 206 informants. Herbs (49.19%) were the most dominant growth form, and leaves (49.19%) were the most common plant parts used for the preparation of herbal medicine while decoction (61.21%) was the most popular formulation. Asteraceae (11) were the most common families among the documented species. Digestive disease, burns, cuts, and wounds had the highest ICF value (0.94), and Lepionurus sylvestris had the highest FL (91%). Oroxylum indicum (6.25) was the most commonly utilized ethnomedicinal plant based on UV, RI had the highest value in Blumea lanceolaria (1.12), and O. indicum (0.29) had the highest RFC value. According to the findings, the traditional medicinal plant treatment is still widely used in the research area. Conclusion Documentation of new ethnomedicinal species and their therapeutic usage will encourage further phytochemical and pharmacological research, potentially leading to the discovery of new drug formulations.